2014
DOI: 10.1155/2014/564136
|View full text |Cite|
|
Sign up to set email alerts
|

Synergistic Effects of Toxic Elements on Heat Shock Proteins

Abstract: Heat shock proteins show remarkable variations in their expression levels under a variety of toxic conditions. A research span expanded over five decades has revealed their molecular characterization, gene regulation, expression patterns, vast similarity in diverse groups, and broad range of functional capabilities. Their functions include protection and tolerance against cytotoxic conditions through their molecular chaperoning activity, maintaining cytoskeleton stability, and assisting in cell signaling. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 130 publications
0
19
0
Order By: Relevance
“…Hsp27 is involved in cell migration, the architecture of the cytoskeleton, and cell growth [46]. Hsps, particularly Hsp60 and Hsp70, were proposed as biomarkers of exposure to heavy metals and various environmental factors [47]. Liu et al reported that the expression levels of Hsps were induced in the liver of Se-deficient chickens [22].…”
Section: Discussionmentioning
confidence: 99%
“…Hsp27 is involved in cell migration, the architecture of the cytoskeleton, and cell growth [46]. Hsps, particularly Hsp60 and Hsp70, were proposed as biomarkers of exposure to heavy metals and various environmental factors [47]. Liu et al reported that the expression levels of Hsps were induced in the liver of Se-deficient chickens [22].…”
Section: Discussionmentioning
confidence: 99%
“…HSP90 were generally used as biomarkers against metals and organic compounds' stress in marine diatom Ditylum brightwellii. Exposure to different types and doses of copper and nickel compounds was monitored, revealing stimulation of HSP90 gene expression; however the pattern of such stimulation varied (Mahmood et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A variety of cellular stresses induce the nucleocytoplasmic redistribution of various functional proteins and perturbation of conventional nucleocytoplasmic transport pathways (Kose and Imamoto, 2014). HSP70 plays a protective role in cadmium cytotoxicity (Levinson et al, 1980;Mahmood et al, 2014). In this study, HSP70-Ran-RCC1 transport system was induced by cadmium exposure.…”
Section: Resultsmentioning
confidence: 73%
“…Protooncogenes such as c-myc might not be involved in cadmium-induced apoptosis of porcine kidney LLC-PK 1 cells (Ishido et al, 1998), and it has been reported that HSP70 would protect against cadmium cytotoxicity (Levinson et al, 1980;Mahmood et al, 2014). Here, we investigated the effect of cadmium on the HSP70-Ran-RCC1 transport system in porcine kidney LLC-PK 1 cells.…”
Section: Introductionmentioning
confidence: 96%